A Process for Integrating Civil and Architectural Data in the AEC Projects: Case Study in South Korea - Won, Jongsung; Kim, Seonwoo; Kim, Honghyun; Kim, Jaeyub (International Journal of Engineering and Technology, 2018)
This paper aims to propose a process to efficiently integrate and manage architectural and civil data in the design and construction stages of architecture, engineering, and construction (AEC) projects using building information modeling (BIM) and civil information modeling (CIM) technologies. The proposed method helps practitioners to understand complex geometries and unknown spaces of AEC projects by producing accurate integrated models, thereby reducing the number of design and construction errors detected on site and improving the process of decision making. It can integrate drawings of architectural and civil elements, drawings and maps of geology and topography of earth, 3D survey results, and other measured data. In order to validate the applicability of the proposed process, it was applied to the Gwangmyeong Cave project in South Korea. In the case, dozens of GB of 3D survey data were successfully converted to a less than 100 MB BIM model.Â Â